KAJIAN TENTANG KONVERGENSI INTERNATIONAL FINANCIAL REPORTINGSTANDARD (IFRS) DI INDONESIA - Suyatmini Suyatmini; Aisya Sheilla FN (Jurnal Pendidikan Ilmu Sosial, 2014)
The aim and main target of the study is to know the advantages of IFRS convergencein Indonesia, the impact that is appeared, barrier that is faced, and the way toovercome. The approach that is used qualitative descriptive. Data that is usedqualitative. While data sources that is used library literatures that is closed relation with thetopic and relevant written document. The research result show that the benefits of IFRSconvergence are: 1. to ease the understanding of financial reporting by using standardfinancial accounting that is known internationally (enhance comparability), 2. to increaseglobal investment stream through transparancy, 3. to decrease capital budget by openingfund raising through capital market globally, 4. to create eficient financial reportingarrangement, and 5. to increase financial reporting quality. The appeared impact that iscaused by IFRS convergence are; 1. mind stream changing from rule-based to principlebased,2. international butgetting accses will be opened because financial reporting will beeasier to communicate to global investors, 3. The relevance of financial reporting willincrease because using more logical value, etc. The barrier that is faced during IFRSconvergence are: 1. Accounting standard board that is lacked of human resource, 2. highbudgetting to adopt IFRS. That impact can be overcome by preparing qualified humanresources that have IFRS capability and developing a good integration system